Is early-onset in major depression a predictor of specific clinical features with more impaired social function? - Liu Y. (Chinese Medical Association, 2015)
© 2015, Chinese Medical Association. All Rights Reserved. Background: Early-onset major depressive disorder (MDD) (EOD) is often particularly malignant due to its special clinical features, accompanying impaired social function, protracted recovery time, and frequent recurrence. This study aimed to observe the effects of age onset on clinical characteristics and social function in MDD patients in Asia. Methods: In total, 547 out-patients aged 18–65 years who were from 13 study sites in five Asian countries were included. These patients had MDD diagnose according to the Diagnostic and Statistical Manual of Mental Disorders, 4th Edition criteria. Clinical features and social function were assessed using Symptom Checklist-90-revised (SCL-90-R) and Sheehan Disability Scale (SDS). Quality of life was assessed by a 36-item Short-form Health Survey (SF-36). Analyses were performed using a continuous or dichotomous (cut-off: 30 years) age-of-onset indicator. Results: Early-onset MDD (EOD, <30 years) was associated with longer illness (P = 0.003), unmarried status (P < 0.001), higher neuroticism (P ≤ 0.002) based on the SCL-90-R, and more limited social function and mental health (P = 0.006, P = 0.007) based on the SF-36 and SDS. The impairment of social function and clinical severity were more prominent at in-patients with younger onset ages. Special clinical features and more impaired social function and quality of life were associated with EOD, as in western studies. Conclusions: EOD often follows higher levels of neuroticism. Age of onset of MDD may be a predictor of clinical features and impaired social function, allowing earlier diagnosis and treatment.